When you need a lift eaudiobook But don't want to eat chocolate, pay a shrink, or drink a bottle of gin. - Behar, Joy (Tantor Media, 2007)
Joy Behar, comedian and cohost of ABC's The View , offers a follow-up to her Joy Schtick with this compilation written by 100 of her friends, associates, and role models, including Barbara Bush, Donald Trump, and James Earl Jones. Behar asked her celebrity friends to share whatever picks them up when they're down in the dumps, and as each celebrity offers his or her advice on how to cope with the blues, it soon becomes clear that most of us are driven to find solace in similar activities, regardless of who we are.